Investigating Secondary Students’ Perceptions of Curriculum Complexity and Instructional Challenges in English Language Acquisition in Nepal - Jora, Man Bahadur (SNPRC Journal, 2025)
The present study investigates the problems encountered by secondary level students in learning the English language. The main objectives of this study were to identify the main problems faced by students in learning English at the secondary level and to identify the major difficulties experienced by students and the factors responsible for those difficulties. The study was a qualitative research design employing transcendental phenomenological research. Data were collected from secondary level students of selected schools using interview guidelines and themes were derived employing thematic analysis. The collected data were analyzed through thematic analysis. Learners find it difficult to grasp new English words because of a lack of adequate contextual information, pronunciation difficulties, and multiple meanings, causing apprehension about misusing the words and poor sentence construction, particularly for foreign students in Nepal. The less use of Nepalese cultural materials in textbooks causes a gap, making the textbooks seem foreign and uninteresting, especially for minority groups. Learning environments are devoid of speaking practice due to teacher-led approaches, crowded classrooms, and examination-oriented curricula, causing apprehension, passive learning, and poor speaking fluency. Moreover, monotonous writing activities without proper schemes and constructive comments hamper creative expression, leaving learners with mechanical skills but poor coherence and autonomy.